Ґендерні студії в контексті структурної методології і кібернетичної реальності - Повторєва, Світлана; Шадських, Юрій (Видавництво Львівської політехніки, 2014)
Доведено, що ґендерні дослідження грунтуються на принципах структурної методології. Показано, що ці принципи застосовуються в жіночих студіях (зорема українських). Розкривається зв’язок феміністичних проектів з можливостями кіберсвіту. The aim of this article is to show, on the grounds of using the main principles of structural analysis in gender studies, its constructive possibilities, its ability to clear out the basic contradictions and conflicts which are declared in the discourse of the modern West European and oriented to it (Ukrainian, American and so on) humanitarian studies and outline its real softening and further solution. First of all, the author proves that the gender studies both in the previous days and nowadays are based on the structural methodology. Accent had been done on the specification of the Ukrainian gender studies and their relations to this methodology. The usage of the comparative and semiotic methods helps to discover the function specification ofstructural methodology in the gender studies. The article demonstrates that the structural methodology is applied in gender studies due to its theoretic and practical effectiveness. The basic idea is shown in the the thesis that the social world is made from the meanings constructed and adopted by people. There is, of course, some conditions which dont depend on perception but facts are not neutral, they demand interpretation in the context of values of existing systems meanings. This methodology first of all promote the informed practical work and try to change the world by invading in constantly changing hided structures. In particular the practical character of the feminist studies is directed on women’ interests in their subjectivity. This study is aimed to implement feminist projects and to realize the ideals of women movement. The results of this investigation create the possibilities to use the principles of structural methodology on every field of the humanitarian sciences, literature and art, to construct the method of analysis of modern discourse practices.
Gender study in the context of structural methodology concerning cybernetic reality
Keywords: відмінність; ґендер; деконструкція; жіночі студії; кіборги; структурна методологія; трансгресія; difference; gender; deconstruction; female study; kyborgs; structural methodology; transgression